Ameliorating Effects of Biochar, Sheep Manure and Chicken Manure on Acidified Purple Soil - Jingjing Chen; Junfeng Yu; Zhongyi Li; Jia Zhou; Linqing Zhan (Agronomy, 2023)
The proportion of acidic purple soils has increased. Consequently, an effective method for amelioration of acidic purple soils is urgently needed. A 40 day incubation experiment using apple tree biochar, fermented sheep manure and chicken manure was conducted to assess the effects of organic materials on the acidity and fertility of acidic purple soil. The results showed that application of organic materials increased soil pH and decreased soil-exchangeable acidity. All of the treatments increased soil-exchangeable and water-soluble base cations after incubation. Specifically, biochar increased soil pH and reduced exchangeable acidity more than the other two fermented manures, because biochar was rich in carbonates and other alkaline substances. The concentration of soil available K was significantly higher under biochar than manure addition, while the opposite was true for soil available P and N, with a higher increase in soil available P in the manure treatments. By evaluating the soil fertility using a fuzzy comprehensive method, it was found that the fermented livestock manure enhanced soil fertility more strongly than biochar. Considering the effectiveness of soil amendments and production cost, applying a large amount of fermented organic fertilizer is an effective approach to the amelioration of acidified purple soil.